1998
DOI: 10.1212/wnl.51.2.371
|View full text |Cite
|
Sign up to set email alerts
|

Campylobacter jejuni lipopolysaccharides in Guillain-Barré syndrome

Abstract: These results indicate that patients who develop GBS respond differently to the ganglioside-like epitopes on Campylobacter than do non-GBS diarrhea patients. Our findings support a role for host susceptibility as a determinant for the outcome following Campylobacter infection. These findings have important implications for the development of vaccines against Campylobacter jejuni.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
70
0
3

Year Published

1999
1999
2006
2006

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(75 citation statements)
references
References 14 publications
2
70
0
3
Order By: Relevance
“…Of the enteritis-associated strains, half had LPSs which had GM 1 epitopes, and thus mimicry of ganglioside GM 1 by core OS of C. jejuni strains is not limited to strains associated with GBS. This phenomenon has previously been reported by a number of groups (29,34,39,46,51). A study by Nachamkin et al (34) showed that 26% of enteritis isolates were positive for the GM 1 -like epitope.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Of the enteritis-associated strains, half had LPSs which had GM 1 epitopes, and thus mimicry of ganglioside GM 1 by core OS of C. jejuni strains is not limited to strains associated with GBS. This phenomenon has previously been reported by a number of groups (29,34,39,46,51). A study by Nachamkin et al (34) showed that 26% of enteritis isolates were positive for the GM 1 -like epitope.…”
Section: Discussionsupporting
confidence: 72%
“…A study by Nachamkin et al (34) showed that 26% of enteritis isolates were positive for the GM 1 -like epitope. Patients who develop enteritis and have isolates with ganglioside-mimicking LPS do not develop antiganglioside antibodies (37,43,51). The humoral immune response to neural cross-reactive epitopes in the LPSs of C. jejuni appears to be different in GBS than in uncomplicated enteritis (51).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients are frequently exposed to Campylobacter; however, only 1 in 1000 develops GBS following infection (21). This strongly suggests that host susceptibility plays an important role in the development of GBS following infection (22).…”
Section: G Uillain-barré Syndrome (Gbs)mentioning
confidence: 99%
“…Studies in this area, however, are scattered and inconclusive. For example, several reports documented the involvement of host factors in certain patients that contributed to the failure to develop antiganglioside antibodies in the pathogenesis of GBS (72). Hartung and Toyka (34) reported macrophage activation in GBS in which circulating activated T lymphocytes were found, as evidenced by augmented expression of histocompatibility antigens (HLA-DR), suggesting that there is an association between GBS and HLA alleles.…”
Section: Genetic Predisposition Of Gbsmentioning
confidence: 99%